2011
DOI: 10.1177/000313481107700709
|View full text |Cite
|
Sign up to set email alerts
|

Parastomal Small Bowel Evisceration as a Result of Parastomal Pyoderma Gangrenosum in a Patient with Crohn's Disease

Abstract: Brief Reports should be submitted online to www.editorialmanager.com/ amsurg. (See details online under ''Instructions for Authors''.) They should be no more than 4 double-spaced pages with no Abstract or sub-headings, with a maximum of four (4) references. If figures are included, they should be limited to two (2). The cost of printing color figures is the responsibility of the author.In general, authors of case reports should use the Brief Report format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Table 1 [ [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] summarizes the 17 cases of parastomal and transstomal evisceration. Of the 17 cases identified from the literature review, 14 (82%) were male with a median age of 62 years.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 [ [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] summarizes the 17 cases of parastomal and transstomal evisceration. Of the 17 cases identified from the literature review, 14 (82%) were male with a median age of 62 years.…”
Section: Discussionmentioning
confidence: 99%
“…Seven different options were used for surgical stoma treatment, demonstrating a high versatility: stoma revision/refashion [20][21][22]24,25,27,28,30,37]; partial resection and recreation of initial stoma [19,29,[31][32][33]; repair of tansstomal defect [14,18,34,35]; repositioning to a new site [15,16,23,36]; conversion to another type of stoma in the same location [12,17]; take-down of temporary ileostomy [13]; and stoma resection [23]. The initial stoma site was preserved in 22/28 case reports (78.57%).…”
Section: Surgical Stoma Treatmentmentioning
confidence: 99%
“…Vornehm et al [ 16 ], 2011, reported a late (two years after surgery) SB parastomal evisceration in a 66-year-old female with a long history of Crohn’s disease after Hartmann’s procedure for perforated diverticulitis. Extensive chronic parastomal pyoderma gangrenosum created a large fascial defect.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations